Unveiling the impacts of exposure and social proximity to suicidality on help-seeking behavior among the young generation - Sijia Li; Alvin Junus; Paul Siu Fai Yip (Elsevier, 2024)
Each suicide affects a wide circle of individuals and increases in suicide rate imply that a larger share of the population would be exposed to suicidality. This exposure may alter individuals' tendency to seek help when they face distress and is influenced by social proximity. However, limited evidence has clarified the direct and moderating effect of social proximity to suicidality on help-seeking behavior. Data were collected from a population-representative survey conducted in 2021. We recruited 1501 individuals aged 11-35 years with random sampling through mobile phone numbers. Exposure and social proximity to suicidality were measured as independent variables and help-seeking behaviors were outcomes, along with sociodemographics, psychological distress, and mental health risks as covariates. We employed latent class analysis to identify help-seeking behavior patterns and conducted multinomial logistic regressions with a three-way interaction to investigate the direct and moderating effects of social proximity to suicide ideation (SI), self-harm (SH), and suicide attempt (SA) on each help-seeking behavior pattern separately. Each unit increase in social proximity to SH was associated with a 30.9% higher likelihood of seeking help from family, friends, and partners even after controlling for distress and mental health risks. Furthermore, the three-way interaction (β123 = 0.041, 95% CI [0.014, 0.069]) suggested joint moderating effects of social proximity among people who did not rely on family. The effect of social proximity to any single stage of suicidality was amplified only when people were not exposed to the other two stages. Closer social proximity to suicidality could heighten the probability of individuals seeking help from family, friends, and partners regardless of distress level, with SH exposure's effects being stronger than SI's and SA's. Initial exposure to any single stage of suicidality could have a stronger effect than subsequent exposures among individuals who did not rely on family.